Drying Process Optimization and Efficiency of Aluminum Fluoride (AlF3) Plant - Hanifah Inas Nastiti; Ryan Anindya Affan; Elly Agustiani (Institut Teknologi Sepuluh Nopember, 2022)
Aluminum Fluoride (AlF3) is a substantive material used to reduce the melting point temperature of the Aluminum from 1500oC to 600-850oC. The production applies a wet process using raw materials of Fluosilicic Acid and Aluminum Hydroxide with a by-product of Silica Dioxide. In this case, AlF3 products are expected to have a maximum H2O content of 2.6%. However, in the production process, the H2O content reached 3% due to the inoptimum drying process. Therefore, the optimization process was carried out by increasing the dry air temperature of the recycle from stage 2 to stage 1 in the drying process, so that the mass transfer of H2O from AlF3 crystals to the air can be maximized. After the optimization, it was found that the H2O content has met the quality standard of 1.8%.